(untitled) (International Journal of Business Innovation, 2024)
The aim of this article is to analyze scientific production on impression management, presenting articles published by year, title of origin, citation, type of document, as well as identifying publications by author, affiliation, country, subject and type. For this purpose, the bibliometric analysis methodology was followed, using the keywords "Impression Management" and establishing the research criteria in the first instance, after which some filters were applied to the results obtained. The main conclusions of this study show that the year with the most scientific research was 2019 and the year with the most citations was 2022. Accounting Auditing and Accountability Journal, International Journal of Business Communication, Journal of Management and International Business Review stood out in terms of publication. The sample of scientific articles was more comprehensive than the re-views. It was possible to verify the presence of co-authorship between authors. Finally, with regard to the documents published by country, the United States of America, the United Kingdom and Australia stood out.